URGENSI PENCATATAN SIPIL DALAM PEMENUHAN HAK ANAK TELAAH MENURUT IMAM SYAFI’I DAN HAM - Zamroni, Mohammad (Musawa Jurnal Studi Gender dan Islam, 2015)
The Urgency of Civil Registration in the Fulfilment of the Rights of the Child From birth Indonesian children have the basic right to be protected by the State and according to religion. One of the basic rights of the child is the right to obtain a birth certificate through the civil registration system. In this context, all children are seen to have the same basic human rights, and the same is true according to Islam. For example, there is no differentiation in relation to whether a child is born within marriage or illegitimately. From a human rights perspective, all children have an equal rights. Similarly, in Islamic jurisprudence according to the Imam Shafi’i School there are no limits to the care of a child. Civil registration of birth ensures human rights in relation to social status and individual benefits. The civil registration system gives individuals a unique identity, records the relationship with parents, and provides the foundation for citizenship. Birth certificates provide documentation of the birth of the child and usually one or both parents, which was fundamental to the determination of nationality, depending on the laws of each country. Civil registration is also important in recording death, marriage, divorce and so forth.